OPTIMIZATION OF GROWTH CONDITIONS AND PURIFICATION OF QUORUM SENSING SIGNAL MOLECULES PRODUCED BY PSEUDOMONAS AERUGINOSA - LOKENDER KUMAR; RAVI KUMAR GUPTA; SANJAY CHHIBBER; KUSUM HARJAI (International Journal of Pharma and Bio Sciences, 2013)
Expression of virulence factors and biofilm formation in P.aeruginosa is associated with production of quorum sensing signal molecules (QSSMs) belonging to the class of acyl homoserine lactones (AHLs). Besides regulating virulence factors, these molecules also interact with eukaryotic cells and can modulate immune response. In most of the studies, synthetic QSSMs have been employed as therapeutic agents. Although 98-99% homology exist between synthetic and natural AHLs but the biological response against either may in fact be different in natural host. In the present study, under optimized growth conditions there is increase in the production of natural AHLs. Extracted AHLs were detected using C18 reverse phase analytical thin layer chromatography (RP TLC) by employing Agrobacterium tumefaciens as biosensor strain. Preparative TLC assay was successfully performed to purify the 3oxo-C12-HSL and 3-oxo-C10-HSL. This study provides easy and simple method for purification of natural AHLs under optimized conditions, hence these molecules can be employed for future research involving control of infections associated with P.aeruginosa.